(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
The digital economy has emerged as a key driver of globalization, reshaping international economic interactions and facilitating deeper integration among nations. This article explores the impact of the digital economy on international economic integration, focusing on its role in enhancing trade, investment, and cooperation among nations. It discusses the challenges and opportunities presented by the digital economy, and highlights the importance of policies and regulations in harnessing its potential for promoting inclusive and sustainable growth